CYP2C19 metabolizer phenotypes may affect the efficacy of statins on lowering small dense low-density lipoprotein cholesterol of patients with coronary artery disease - Dai, Ruozhu; Zhao, Xiaoyu; Zhuo, Huilin; Wang, Wei; Xu, Yue; Hu, Zixin; Zhang, Tiexu; Zhao, Jiangman (Frontiers in Cardiovascular Medicine, 2022)
Background Dyslipidemia is a major cause of arteriosclerotic cardiovascular disease (ASCVD), and low-density lipoprotein cholesterol (LDL-C) is the profile to be reduced to prevent disease progression. Small dense low-density lipoprotein cholesterol (sdLDL-C) has been proven to be a more effective biomarker than LDL-C for ASCVD primary and secondary prevention. CYP2C19 is an important drug metabolism gene. This study aimed to investigate the relationship between sdLDL-C and coronary artery disease (CAD) risk factors and explore the influence of CYP2C19 metabolizer phenotypes on the sdLDL-C lowering efficacy of statins. Methods This study recruited 182 patients with CAD and 200 non-CAD controls. Baseline laboratory indices of fasting blood were detected, including blood lipids, glucose, and creatinine. In addition, LDL-C subfractions were separated and quantified. Gene polymorphisms of SLCO1B1 and CYP2C19 were detected in patients with CAD. The LDL-C subfractions levels of patients with CAD were followed up after statin drug treatment. Results Total cholesterol, LDL-C, LDLC-2, LDLC-3, LDLC-4, LDLC-5, LDLC-6, LDLC-7, and sdLDL-C levels of patients with CAD were significantly higher than those in non-CAD controls. Meanwhile, sdLDL-C (AUC = 0.838) and LDLC-4 (AUC = 0.835) performed outstandingly in distinguishing patients with CAD from controls. Based on CYP2C19 metabolizer phenotypes, 113 patients with CAD were divided into the extensive metabolizer (EM, n = 49), intermediate metabolizer (IM, n = 52), and poor metabolizer (PM, n = 12) groups. The patients with IM and PM metabolizer phenotypes had better sdLDL-C lowering efficacy after taking statin drugs than patients with EM phenotype (P = 0.0268, FDR = 0.0536). The SLCO1B1 genotype had no significant impact on the efficacy of statins (P = 0.1611, FDR = 0.1611). Conclusion sdLDL-C and LDLC-4 outperformed other blood lipids such as LDL-C for CAD risk screening. CYP2C19 metabolizer phenotypes had the potential to predict the efficacy of statins in lowering sdLDL-C.